Rift foundering and the generation of non-orogenic granulites during the Mesoproterozoic - Jie Yu; Ben S. Knight; Chris Clark; Christopher L. Kirkland; Martin Hand (Earth and Planetary Science Letters, 2025)

Dust in the Critical Zone: North American case studies - J. Brahney; R.C. Heindel; T.E. Gill; G. Carling; J.M. González-Olalla; J. Hand; D.V. Mallia; J.S. Munroe; K. Perry; A.L. Putman; S.M. Skiles; B.R. Adams; et al. (Earth-Science Reviews, 2024)

Analysis of Registered Dietitian Nutritionists (RDNs) Knowledge, Attitudes, and Beliefs on Transgender Nutrition Care in Michigan - J. Ford; E. Colling; D. Hannah; S. Hand (Journal of the Academy of Nutrition and Dietetics, 2024)

10 keV electron irradiation of methane ices at ocean world surface temperatures - Michael S. Bramble; Kevin P. Hand (Icarus, 2024)

The effect of in-situ metasomatism on the electrical resistivity of the lower crust - S. Jennings; D. Hasterok; M. Hand; K. Bhowany (Physics of the Earth and Planetary Interiors, 2023)

Development and application of a new liver pathology recording system for use in cattle abattoirs - Helen Owen; Emily Jones; Carla Kowald; Sebastian Hand; Michael McGowan; Rowland Cobbold; Tamsin S. Barnes; Justine S. Gibson; Shahab Ranjbar; Chiara Palmieri; Rachel Allavena (Research in Veterinary Science, 2023)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Anatomical and biochemical studies of Spartium junceum infected by Xylella fastidiosa subsp. multiplex ST 87 - S. Falsini; C. Tani; G. Sambuco; A. Papini; P. Faraoni; S. Campigli; L. Ghelardini; G. Bleve; D. Rizzo; M. Ricciolini; I. Scarpelli; L. Drosera; et al. (Protoplasma, 2022)
Spartium junceum L. is a typical species of Mediterranean shrubland areas, also grown in gardens and parks as an ornamental. In recent years in Europe, S. junceum has been recurrently found to be infected by different subspecies and genotypes of the quarantine regulated bacterium Xylella fastidiosa (Xf). This work presents for the first time the anatomy of S. junceum plants that we found, by means of genetic and immunochemistry analysis, to be naturally infected by Xf subsp. multiplex ST87 (XfmST87) in Monte Argentario (Grosseto, Tuscany, Italy), a new outbreak area within the EU. Our anatomical observations showed that bacteria colonized exclusively the xylem conductive elements and moved horizontally to adjacent vessels through pits. Interestingly, a pink/violet matrix was observed with Toluidine blue staining in infected conduits indicating a high content of acidic polysaccharides. In particular, when this pink-staining matrix was observed, bacterial cells were either absent or degenerated, suggesting that the matrix was produced by the host plant as a defense response against bacterial spread. In addition, a blue-staining phenolic material was found in the vessels and, at high concentration, in the pits and inter-vessels. SEM micrographs confirmed that polysaccharide and phenolic components showed different structures, which appear to be related to two different morphologies: fibrillary and granular, respectively. Moreover, our LM observations revealed bacterial infection in xylem conductive elements of green shoots and leaves only, and not in those of other plant organs such as roots and flowers.

The role of local sea surface temperature pattern changes in shaping climate change in the North Atlantic sector - Ralf Hand; Noel S. Keenlyside; Nour-Eddine Omrani; Jürgen Bader; Richard J. Greatbatch (Climate Dynamics, 2019)

Assessments of species’ vulnerability to climate change: from pseudo to science - Alisa A. Wade; Brian K. Hand; Ryan P. Kovach; Clint C. Muhlfeld; Robin S. Waples; Gordon Luikart (Biodiversity and Conservation, 2017)

Mechanisms of endosperm initiation - Philip Hands; David S. Rabiger; Anna Koltunow (Plant Reproduction, 2016)

Climate variables explain neutral and adaptive variation within salmonid metapopulations: the importance of replication in landscape genetics - Brian K. Hand; Clint C. Muhlfeld; Alisa A. Wade; Ryan P. Kovach; Diane C. Whited; Shawn R. Narum; Andrew P. Matala; Michael W. Ackerman; Brittany A. Garner; John S. Kimball; Jack A. Stanford; Gordon Luikart (Molecular Ecology, 2016)
Understanding how environmental variation influences population genetic structure is important for conservation management because it can reveal how human stressors influence population connectivity, genetic diversity and persistence. We used riverscape genetics modelling to assess whether climatic and habitat variables were related to neutral and adaptive patterns of genetic differentiation (population‐specific and pairwise F ST ) within five metapopulations (79 populations, 4583 individuals) of steelhead trout ( Oncorhynchus mykiss ) in the Columbia River Basin, USA . Using 151 putatively neutral and 29 candidate adaptive SNP loci, we found that climate‐related variables (winter precipitation, summer maximum temperature, winter highest 5% flow events and summer mean flow) best explained neutral and adaptive patterns of genetic differentiation within metapopulations, suggesting that climatic variation likely influences both demography (neutral variation) and local adaptation (adaptive variation). However, we did not observe consistent relationships between climate variables and F ST across all metapopulations, underscoring the need for replication when extrapolating results from one scale to another (e.g. basin‐wide to the metapopulation scale). Sensitivity analysis (leave‐one‐population‐out) revealed consistent relationships between climate variables and F ST within three metapopulations; however, these patterns were not consistent in two metapopulations likely due to small sample sizes ( N = 10). These results provide correlative evidence that climatic variation has shaped the genetic structure of steelhead populations and highlight the need for replication and sensitivity analyses in land and riverscape genetics.

Genetic map construction and QTL mapping of resistance to blackleg (Leptosphaeria maculans) disease in Australian canola (Brassica napus L.) cultivars - S. Kaur; N. O. I. Cogan; G. Ye; R. C. Baillie; M. L. Hand; A. E. Ling; A. K. Mcgearey; J. Kaur; C. J. Hopkins; M. Todorovic; H. Mountford; D. Edwards; et al. (Theoretical and Applied Genetics, 2009)

Alpha e-taxonomy: responses from the systematics community to the biodiversity crisis - S. J. Mayo; R. Allkin; W. Baker; V. Blagoderov; I. Brake; B. Clark; R. Govaerts; C. Godfray; A. Haigh; R. Hand; K. Harman; M. Jackson; et al. (Kew Bulletin, 2008)

Anoxia tolerance of con-familial tiger beetle larvae is associated with differences in energy flow and anaerobiosis - W. W. Hoback; J. E. Podrabsky; L. G. Higley; D. W. Stanley; S. C. Hand (Journal of Comparative Physiology B, 2000)

Characterization of ATP-dependent proteolysis in embryos of the brine shrimp, Artemia franciscana - F. van Breukelen; S. C. Hand (Journal of Comparative Physiology B, 2000)

Novel mutations in the 3' region of the polycystic kidney disease 1 (PKD1) gene - A.R. Afzal; M. Hand; E. Ternes-Pereira; A. Saggar-Malik; R. Taylor; S. Jeffery (Human Genetics, 1999)

Novel mutations in the 3' region of the polycystic kidney disease 1 (PKD1) gene - A.R. Afzal; M. Hand; E. Ternes-Pereira; A. Saggar-Malik; R. Taylor; S. Jeffery (Human Genetics, 1999)

Physiological response to complex environments in annual Polygonum species of contrasting ecological breadth - S. E. Sultan; A. M. Wilczek; D. L. Bell; G. Hand (Oecologia, 1998)